Effect of Various Additives on Photocatalytic Degradation of 4-Nitrophenol - Kashif Naeem; Feng Ouyang (E-Journal of Chemistry)
The photocatalytic degradation of 4-nitrophenol (4-NP) assisted by titanium dioxide (TiO2) was investigated in aqueous suspension under irradiation by UV light. The effect of different supporting materials mixed physically with TiO2on the photocatalytic degradation of 4-NP has been studied. TiO2 with all supports exhibits good degradation efficiency of 4-NP and was better than TiO2 alone. The addition of SiO2 and ZSM-5 only caused a little change in 4-NP degradation. However, degradation of 4-NP was improved from 34.89% to 60.53% within 120 min photocatalysis in the presence of optimal amount of AC. The degradation was also fairly enhanced in the presence of cheaper rice husk and the activity was closed to AC.